2008
DOI: 10.1177/014556130808700914
|View full text |Cite
|
Sign up to set email alerts
|

Lipoid Proteinosis (Urbach-Wiethe Disease): A Case Report from India

Abstract: Lipoid proteinosis (Urbach-Wiethe disease) is a rare autosomal-recessive anomaly that primarily affects the skin and the mucosa of the upper aerodigestive tract in children. It is caused by hyaline deposits in tissues. Hoarseness secondary to laryngeal involvement is frequently the first presenting feature. It is important to consider this disease in the differential diagnosis of hoarseness because it might lead to life-threatening airway compromise. We report a case of lipoid proteinosis in a 12-year-old girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Fourteen patients (70%) had a better voice; but unfortunately, in most cases, nothing is known about the duration of the improvement. 1,[25][26][27][28][29] In two patients (10%) (one laser and one cold instruments), the voice was better for several months, but recurrence was documented. 17,30 One patient (5%) had no improvement, 31 and one study described improved of stridor, but not of hoarseness after laser excision.…”
Section: Surgerymentioning
confidence: 99%
“…Fourteen patients (70%) had a better voice; but unfortunately, in most cases, nothing is known about the duration of the improvement. 1,[25][26][27][28][29] In two patients (10%) (one laser and one cold instruments), the voice was better for several months, but recurrence was documented. 17,30 One patient (5%) had no improvement, 31 and one study described improved of stridor, but not of hoarseness after laser excision.…”
Section: Surgerymentioning
confidence: 99%
“…Hence, review of 51 cases of LP reported in India from 1969 to 2021 is done along with the present case [ Table 1a – c ]. [ 1 4 5 6 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] LP is more reported in patients in the age group of 11-20 (51%). More prevalence of LP is reported in males (70.6%).…”
Section: Review and Discussionmentioning
confidence: 99%
“…On review of oral manifestations, 42 cases were found as shown in Table 1c . [ 1 4 5 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 25 26 27 28 29 30 31 32 33 34 35 37 38 39 42 43 44 ] The most common involved site is tongue with typical thick woody appearance followed by restricted tongue movements. In the present case, also similar findings were present.…”
Section: Review and Discussionmentioning
confidence: 99%
“…Lipoid proteinosis (LP) is known as Urbach-Wiethe syndrome or hyalinosis cutis et mucosae and was first reported by dermatologist and otolaryngologist duo Urbach and Wiethe in 1929 [1]. LP is a rare entity with autosomal recessive inheritance and multiple system involvement causing dermatological, otorhinolaryngological, ocular, and neurological manifestations.…”
Section: Introductionmentioning
confidence: 99%